Application of Student-Centered Activities Among Engineering Students in the New Norm of Learning - Vitobina, Crugie Boy; Briones, John Robert G.; Ramos Jr., Michael M.; Enrico, Kenneth (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This action research aimed to implement the blended learning modality through student-centred activity in the new normal of the engineering department of the Cavite State University – CCAT Campus. The study utilized quasi-experimental research design. Inferential and observation design were utilized to augment and support the research design findings. The Center for Educational Effectiveness at the University of California, Davis, provided the researchers with the checklists, questionnaires with Likert scales, and field and observation notes. Results showed that there was significant difference among the means observed as caused by the intervention. The action research concluded that there is an increase in student’ cognitive, affective, and psychomotor domains after the intervention, and the research identified that asynchronous classes and time management allotted for students were the critical challenges.